Norms for multivariate diagnosis of nutrient imbalance in Arabica and Robusta coffe in the East African highlands - Wairegi, L.W.I.; Asten, Piet J.A. van (Cambridge University Press, 2012)
Poor soil fertility is a constraint to coffee production. Targeting fertiliser recommendations to nutrient deficiencies can contribute to improved crop response to fertiliser. This study aimed to derive and compare the Compositional Nutrient Diagnosis (CND) and Diagnosis and Recommendation Integrated System (DRIS) norms for Arabica and Robusta, and to investigate nutrient interactions using data derived from 164 plots. The high-yield sub-populations of Arabica had significantly (p < 0.01) higher P (0.23 vs. 0.14) and K (2.87 vs. 2.04), and lower N (2.96 vs. 3.61), Ca (0.99 vs. 1.50) and Mg (0.40 vs. 0.23) than those of Robusta.With respect to the CND norms, Arabica had significantly (p < 0.001) higher P and K, and lower N, Ca and Mg means of row-centered log ratios than Robusta. The relationship between the CND and DRIS indices had coefficient of determination (R2) = 0.75–0.99 for both coffee types. The relationship between nutrient imbalance indices for CND and DRIS had R2 of 0.95 (Arabica) and 0.76 (Robusta). Both coffee types had negative N–Ca, P–Mg and K–Mg interactions. Arabica had positive N–Mg and K–Ca interactions and Robusta had positive N–K, P–K and Ca–Mg interactions and negative N–P, N–Mg, P–Ca and K–Ca interactions. The study concludes, there is a need for cultivar-specific norms, but such norms developed under one set of conditions may not be applicable under different conditions. The study also concludes that both CND and DRIS can be used to determine nutrient imbalances, and fertiliser requirements could be cultivar-specific.